Effectiveness of synbiotic yogurt made from pisang batu (musa balbisiana) flour on blood glucose levels and cholesterol levels in type 2 diabetes mellitus patients - Yuniarti Yuniarti; Arintina Rahajuni; Estuasih Dyah Pertiwi; Nurul Fatih Rahmadina (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2026)
ABSTRACTBackground: Type 2 diabetes mellitus (T2DM) is characterized by high blood sugar due to problems with insulin secretion or action. Patients with diabetes often experience dyslipidemia, affecting cholesterol levels. Synbiotic yogurt fermented with Lactobacillus bulgaricus and Streptococcus thermophilus can lower cholesterol through short-chain fatty acids (SCFAs) production. Adding Pisang Batu (Musa balbisiana) flour, a source of fructo-oligosaccharides (FOS), enhances propionic acid in the yogurt, which may improve insulin resistance in metabolic syndrome.Objective: to determine the effect of synbiotic yogurt with banana flour (M. balbisiana) on blood glucose levels and cholesterol levels in patients with type 2 diabetes mellitus who are outpatients at the KMRT Wongsonegoro Regional Hospital.Materials and Methods: A Randomized Controlled Trial (RCT) with a pretest–posttest control group design was conducted on 47 outpatients with type 2 diabetes mellitus at KMRT Wongsonegoro Hospital. The study consisted of 24 patients in the treatment group who were given 300 ml of synbiotic yogurt per day for 4 weeks and 23 patients in the control group. Data analysis used the paired t test.Results: Results showed a significant reduction in blood glucose in the treatment group (8.72 ± 23.51 mg/dL, p = 0.000), while the control group had a slight increase (-3.35 ± 17.20 mg/dL, p = 0.005). The difference between groups in glucose reduction was also significant (11.07 ± 7.08 mg/dL, p = 0.000). However, there was no significant difference in cholesterol levels between the groups (p = 0.224).Conclusion: giving 300 ml of synbiotic yogurt with banana flour every day for 4 weeks was effective in reducing the patient's blood glucose levels but was not effective in reducing cholesterol levels.Keywords : Blood glucose; cholesterol; diabetes mellitus; pisang batu (Musa balbisiana) flour